Effect of protected fat, yeast, niacin, zinc and chromium supplementation on the productive performance of heat-stressed Karan Fries heifers - Purwar, Vaibhav (Indian Journal of Dairy Science, 2018)
The main aim of this study was to evaluate the effect of feed supplements and additives on the productive performance of growing heifers during summer season. A total of 18 Karan Fries (KF) heifers were randomly selected and divided into two groups, i.e. control and treatment. The basal ration for both control and treatment groups was the same. However, the treatment group was supplemented with protected fat, yeast, niacin, zinc, and chromium. Various body growth-related parameters and plasma Insulin-like growth factor 1 (IGF-1) were estimated fortnightly up to 120 days post-feeding. The body weight, DMI/100kg BW and gain in height were numerically higher in the treatment group as compared to control group but it didn’t show any significant difference. Average daily gain (ADG) and heart girth gain (HGG) were significantly (P<0.05) higher in the treatment group as compared to control group. Although the gain in body length was not different between the groups, the overall mean value was significantly (P<0.05) higher in the supplemented group. Unlike ADG and HGG which took two months to exhibit significant difference, plasma IGF-1 showed significant (P<0.01) difference within the first-month post-feeding in the supplemented group as compared to control group. Our findings reveal that the supplementation of above feed package in the ration of KF heifers improves the growth rate under heat stress conditions which are indicated by the higher ADG, body measurements and IGF-1 values in the treatment group.